La produttività del sistema bancario spagnolo negli anni Ottanta: un confronto internazionale - F. PÉREZ GARCÍA; R. DOMÉNECH VILARIÑO (Moneta e Credito, 2013)
In this paper the authors set out to determine whether the present Spanish banking system is as inefficient as previous studies have indicated. In order to achieve this aim they use a methodology similar to that of other researchers who have completed industry studies. They also discuss the evolution of the Spanish banking system during the 1980s.